Urgensi Perlindungan Hak Asasi Anak Atas Data Pribadi di Era Digitilasasi Berdasarkan Prinsip Negara Hukum - Rohmansyah, Duta Agung; Saputra, Kevin Mandela; Sholih, Badrus (Fakultas Syariah INSURI Ponorogo, 2023)
Information related to children in the form of identity names, addresses, photos, videos, and other information about themselves, including their thoughts in speech or pictures, sounds are children's personal data. Children's personal information is shared transparently on social media on various platforms which can be seen, retrieved, even searched for and shared by anyone without adequate legal protection. The research problem to be raised in this study is: How is the protection of privacy rights over personal data in Indonesia implemented? What is the urgency of protecting children's personal data in Indonesia? The normative legal research method is used, namely the primary legal material is collected and analyzed, namely the Child Protection Act, the Information and Electronic Commerce Law and the Personal Data Protection Act. The pattern of approach in this study is carried out using a deductive approach, that is, in general, it is specifically discussed. Based on the research findings, it is known that Article 25 of Law Number 27 of 2022 does not specifically regulate legal mechanisms and forms of protection provided by the State to children who are victims of misuse of their personal data. Because, if we can follow the example of developed countries such as the European Union, the United Kingdom and the United States, they have specific laws in protecting children's personal data so that later when a violation occurs, the existing rules can be properly applied. However, the research was not.